Mamo, tato, co to jest wojna? Czyli jak tłumaczyć wojnę dzieciom, czytając książki - Podskarbi, Witold (Publishing House eBooki.com.pl, 2015)
The aim of this work is to report issues connected with conducting conversations by parents to their children about difficult subjects, such as war, tolerance or ability to coping with own emotions. Above all this work is analyzing chosen books - their fragments or illustrations presenting war conflict. Basic question which matters is - how authors of novels for children presents theme of war: they show it realistically, or escape into fantasy, or they rely on their own memories? All these considerations was complemented by talks with editors from polish publishing houses and also with bibliotherapist from Sri Lanka. Very important part in this discussion are illustrations made by children in preschool age. These illustrations confirm children’s maturity, but first of all confirm that children have need to talk about difficult issues about standing of contemporary world.
Keywords: bibliotherapy; war; books; children’s literature; literature